(3eJWdHGJ GdecJHGJ GdNVQGA (B: s (3OQGSI JNWjWjI aj eUQ (B/s - (3,QMGH LeGd eYhV SYjO s; (3Ced hLjg MeOjs (2024)
(3JdYH GdecJHGJ GdNVQGA OhkQG egkeG aj GdMaGX Ydi GdHjFI hJMbjb GdGSJOGeI GdHjFjI NGUI aj Xd GdJZjjQGJ GdefGNjI GdJj fTgOgG GdBf hGdJj COJ HOhQgG Edi HOA eMGOKI YGdejI ddJcja eY hGbY LOjO jQJHW HJZjQGJ GdHjFI hQDjI eUQ (B2030. (3hef Ke JgOa GdOQGSI Edi Jbjje hGbY JWHjb eaghe hJhLg GdecJHI GdNVQGA HGdecJHGJ GdYQHjI hNGUI GdeUQjI ef MjK ehGUaGJ heYGjjQ JUeje GdeHfj GdCNVQ hGdHjFI GdOGNdjI GdNGUI HgG hPdc aj VhA eG Je ef JLGQH YGdejI hEbdjejI heMdjI heG bO jJjMg Pdc ef Md eTcdGJ GdejRGfjI GdeJfGbUI GdJi JYGfj efgG GdecJHGJ aj GdhWf GdYQHj hGdecJHGJ GdeUQjI Ydi hLg GdNUhU, hcPdc JSYi GdOQGSI Edi hVY EWGQ Yed jecf ddecJHGJ GdeUQjI GdJj JQZH aj Cf JJMhd decJHI NVQGA GdGSJQTGO HgG hGdYed aj EWGQgG(B. (3hJYJeO gPg GdOQGSI Ydi GdefgL GdhUaj HCSdhHg GdeSMj dQUO hGbY JWHjb GdecJHGJ GdNVQGA eSJNOeI COhGJ LeY GdHjGfGJ hgj bGFeI GdeQGLYI ddhbha Ydi GdeYGjjQ hGdehGUaGJ GdeJVefI aj eHGfj GdecJHGJ GdNVQGA, hGdGSJHjGf HZQV JMOjO eOi JMbb eaghe GdecJHI GdNVQGA aj GdecJHGJ GdhGbYI aj fWGb GdOQGSI, hef fJGFL GdOQGSI bdI GdCHMGK aj eLGd GdecJHGJ GdNVQGA NUhkUG GdCHMGK GdYQHjI, ceG Cfg gfGc GdYOjO ef GdfeGPL GdYQHjI GdJj GcJed dOjgG JWHjb eaghe GdecJHI GdNVQGA HfSH eJaGhJI aHYVgG JhGaQ HgG GdeHfi hCNQi JhGaQ HgG GdJLgjRGJ hHYV KGdK HQGeL ddJhYjI(B. (3hbO ChUJ GdOQGSI HVQhQI Cf jchf dOi CNUGFj GdecJHGJ GdeUQjI hGdYQHjI GdhYj GdHjFj HGdJMhd ddCNVQ hEYOGO GdHQGeL GdJYdjejI hGdJhYhjI dJTLjY GdeSJajOjf Ydi JWHjb GdeeGQSGJ GdNVQGA GdeSJOGeI, hGdJQcjR Ydi EYOGO OQGSGJ JJfGhd JhXja GdJbfjGJ GdMOjKI eKd GdPcGA GGdUWfGYj hEfJQfJ GdCTjGA hSdGSd GdcJd (Bblock chain (3aj OYe GdJMhd Edi ecJHGJ NVQGA ShGA HGdfSHI dJhajQ GdWGbI Ch EYGOI JOhjQ GdeNdaGJ Ch fTQ GdhYj GdHjFj Hjf ehXaj GdecJHI hGdeSJajOjf ef NOeGJgG(B. s
Green libraries play an important role in preserving the environment and achieving environmental sustainability, especially in light of the climate changes we are witnessing now, which in turn led to the start of a global conversation to adapt to a new reality and related to environmental changes Egypt Vision 2030. Considering the regional and international experiences that have been made, the study aims to evaluate the reality of applying the concept and orientation of the green libraries in Arabic as well as the Egyptian libraries in terms of specifications and standards for green building design and its internal environment and what this may allow to solve the diminishing budget problems that libraries in the Arab World and Egypt suffer from. The study also will propose an integrated plan as a guide for Egyptian libraries that wish to transform into a green library. The study uses the descriptive approach in its survey style to identify the reality of the green library concept and its application in Egyptian libraries$1 (Bbuildings. The tools are a checklist to identify the standards and specifications included in the buildings of green libraries, and a questionnaire. One of the results of the study is the lack of research in the field of green libraries, especially Arab research, There are also many Arab models that have completed the application of the concept of green library in varying proportions, Some with the availability of the building, others with equipment and some of the third awareness programs, the study recommended that Egyptian and Arab library specialists should have environmental awareness of green transformation and develop educational and awareness programs to encourage beneficiaries to apply sustainable green practices, Focus on preparing studies on the use of modern technologies such as artificial intelligence, the Internet of Things and block chain in support of the transition to green libraries, whether for energy saving, waste recycling or environmental awareness among library staff and beneficiariess
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B97-99.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdecJHGJ GdYGegs; (3GdecJHGJ GdNVQGA s -- (3GdecJHGJ GdeSJOGeIs -- (3GdJfejI GdeSJOGeIs